Configuration and inspection of multi-fixturing pallets in flexible manufacturing systems: Evolution of the Network Part Program approach. (August 2018) - Pellegrinelli, Stefania; Cenati, Claudio; Cevasco, Luca; Giannini, Franca; Lupinetti, Katia; Monti, Marina; Parazzoli, Diego; Molinari Tosatti, Lorenzo
Highlights: Increase of the industrial applicability of the Network Part Program approach, currently used by several companies. Development of a methodology for the automatic design of alternative pallet configuration mounting different part types, increasing production flexibility. Development of a pallet automatic inspection technology for the identification of possible mounting errors, reducing machine tool damages or non-conform parts. Testing of the approach on a real case. Abstract: During last decade, flexible manufacturing systems (FMSs) have moved toward the development of computer aided process planning techniques able to cover the gap among process planning, production planning and scheduling. Among these techniques, the Network Part Program (NPP) approach was able to support the on-line automatic generation of the part programs for multi-fixturing pallets, i.e. fixturing hosting several workpieces. In this context, the proposed approach presents an extension of the NPP in two directions: (i) a pallet configuration module for the automatic generation of alternative pallet configurations, when the workpiece setups are given and different part types are considered; (ii) a pallet inspection module based on laser scanner technology for the automatic identification of possible mounting errors and the automatic evolution of potential resulting errors. The provided extensions increase the flexibility at the shop-floor level in terms of pallet configuration to be machined and the reduction of possible mounting errors due to the increased variability in pallet configurations. The developed approach has been validated on a real case.